2014
DOI: 10.1159/000363492
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Common Treatments Given in the Perinatal Period on the Developing Brain

Abstract: Background: Over the last decades, considerable progress has been made in the perinatal management of high-risk preterm neonates, changing the landscape of pathological conditions associated with neurological impairments. Major focal destructive lesions are now less common, and the predominant neuropathological lesion is diffuse white-matter damage in the most immature infants. Similarly, over the last few years, we have observed a trend towards a decrease in neurological impairment in the absence of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 95 publications
0
14
0
2
Order By: Relevance
“…Recent cohort studies have found an association between the administration of anesthesia in infancy and early childhood NDI, although this association was weakened after adjustment for key covariates, such as perinatal characteristics, indication for anesthesia, and socioeconomic factors [19]. Exposure to neonatal analgesics/sedative drugs can impact the developing brain and neurodevelopmental outcome by the time the child reaches school age [20]. However, clinical data supporting an association between surgery/anesthesia and neurologic impact in preterm infants must be interpreted with caution, even when anesthetic agents have the potential to induce widespread neuroapoptosis through modulation of apoptotic pathways and neurotrophins in animal studies [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent cohort studies have found an association between the administration of anesthesia in infancy and early childhood NDI, although this association was weakened after adjustment for key covariates, such as perinatal characteristics, indication for anesthesia, and socioeconomic factors [19]. Exposure to neonatal analgesics/sedative drugs can impact the developing brain and neurodevelopmental outcome by the time the child reaches school age [20]. However, clinical data supporting an association between surgery/anesthesia and neurologic impact in preterm infants must be interpreted with caution, even when anesthetic agents have the potential to induce widespread neuroapoptosis through modulation of apoptotic pathways and neurotrophins in animal studies [21].…”
Section: Discussionmentioning
confidence: 99%
“…CHF5633, a new synthetic SF, has been described as a potential alternative to natural SF for the treatment of neonatal RDS . Due to the intrinsic relation between ventilation management and cerebral pathology in immature newborns, it is essential to evaluate the influence that a new pulmonary treatment may have on the developing brain. Our findings demonstrate for the first time that administration of new synthetic SF containing SP‐B and SP‐C analogs results in smaller cerebral hemodynamic and oxygen metabolism changes than Curosurf instillation, with neither SF formulation appearing to produce damage to the developing brain in our premature model.…”
Section: Discussionmentioning
confidence: 99%
“…In many premature neonates with RDS, early respiratory care is necessary. However, it has been suggested that some aspects of respiratory care itself are critical factors that may influence the immature brain and the progression toward brain injury . The risks of SF administration include bradycardia and hypoxemia during instillation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rate is approximately 2 per 1,000 live births in Europe. In the era of advanced perinatal therapies, the rates of severe brain injuries and CP have declined in preterm born children [1] . However, CP is still over 30-fold more frequent among very preterm-born compared to term-born children [2] .…”
Section: Introductionmentioning
confidence: 99%